A Local, Grammatically-Annotated Learner Corpus as A Pedagogical Tool - CHRISTINE ANITA XAVIER (The English Teacher, 2017)
This article argues, through a discussion of the different views of 19 teachers, for the usefulness of a local, grammatically-annotated learner corpus as a pedagogical tool for the teaching of grammar in Singapore schools. Several practicing school teachers attended a professional development grammar course which incorporated grammar exercises developed from some data from this corpus. Based on feedback gathered from these teachers via feedback forms, this article suggests that the authentic, contextualized and accessible nature of the learner corpora in question allows teachers to make pedagogical decisions on what grammar components to teach, when to teach them, and how to teach these in the Singapore school context.